Neotropical Nilothauma Kieffer, 1921, with the description of thirteen new species (Diptera: Chironomidae) - Mendes, Humberto Fonseca; Andersen, Trond (Zootaxa, 2009)
Thirteen new species to Nilothauma Kieffer are described and figured: N. amazonense, N. calori, N. complicatum, N. fazzariense, N. involucrum, N. jaraguaense, N. longissimum, N. roquei, N. sooretamense, and N. zitoi from Brazil and N. spiesi from Chile as males, and N. aripuanense and N. matogrossense from Brazil as males and pupae. Type material and other materials of Paranilothauma reissi Soponis, P. strebulosum Adam et Sæther, Neelamia fittkaui Soponis, and N. bergeri Soponis are examined and the males figured. A phylogenetic analysis of all Nilothauma, Paranilothauma Soponis, and Neelamia Soponis species is performed, showing that the genera Paranilothauma and Neelamia should be regarded as junior synonyms of Nilothauma and the included species are placed in Nilothauma as new combinations accordingly. New material further revealed that N. bergeri is a synonym of N. fittkaui. Nilothauma is found in all biogeoraphical regions except Antartica, and shows an Inabrezian (Northern Gondwana) distribution pattern. The phylogeny combined with the corresponding area cladogram and BPA analysis suggests the Neotropical Region as the area of origin.